IDENTIFYING STRESS SIGNATURES ACROSS THE ENGINEERING DESIGN PROCESS: PERCEIVED STRESS DURING CONCEPT GENERATION, CONCEPT SELECTION, AND PROTOTYPING. (May 2020) - Nolte, H.; McComb, C.
Abstract: Various aspects of the design process often lead to stress. This study used pre- and post-task surveys to gather information regarding the designer's cognitive experience, physiological response, and perceived sources of stress during concept generation, concept selection, and prototyping. Results confirmed that design is highly cognitive, and that mental stress is present. Variability in the results also suggests that a physiological stress component might be present. Additionally, perceived sources of stress were examined, and recommendations were offered for instructors of design courses.